2014
DOI: 10.1152/ajpendo.00244.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic portal vein denervation impairs oral glucose tolerance but not exenatide’s effect on glycemia

Abstract: The hepatoportal area is an important glucohomeostatic metabolic sensor, sensing hypoglycemia, hyperglycemia, and hormones such as glucagon-like peptide-1 (GLP-1). We have reported previously that activation of hepatoportal sensors by intraportal infusion of glucose and GLP-1 or by subcutaneous administration of GLP-1 receptor activator exenatide and of intraportal glucose improved glycemia independent of corresponding changes in pancreatic hormones. It is not clear whether this effect is mediated via the port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Recently, Ionut et al have shown, in dogs, that portal denervation decreases glucose tolerance by increasing both glucose and insulin concentrations . Surprisingly, portal denervation did not change the capacity of EX to reduce glucose rate of appearance during OGTT …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, Ionut et al have shown, in dogs, that portal denervation decreases glucose tolerance by increasing both glucose and insulin concentrations . Surprisingly, portal denervation did not change the capacity of EX to reduce glucose rate of appearance during OGTT …”
Section: Discussionmentioning
confidence: 97%
“…Although GLP‐1 is able to activate portal receptors even at low concentrations as those observed during fasting, studies in dogs have shown that stimulation of net HGU is independent of portal GLP‐1 receptors, given that both intraportal and peripheral GLP‐1 infusions were able similarly to stimulate HGU . Recently, Ionut et al have shown, in dogs, that portal denervation decreases glucose tolerance by increasing both glucose and insulin concentrations . Surprisingly, portal denervation did not change the capacity of EX to reduce glucose rate of appearance during OGTT …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Ionut et al. demonstrated that portal vein denervation impairs hypoglycemic counterregulation due to a suppression of the sympathoadrenal response [19] and impaired glucose tolerance has been observed following portal vein denervation during GLP-1 receptor stimulation [20] . Overall, these experiments support that the portal vein is an important sensing site for hypoglycemia and of hormones such as GLP-1.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose 50% was given as a bolus by oral gavage. Blood samples were taken at 15, 30, 45, 60, 90, 120, and 180 min [ 14 ]. Glucose tolerance was measured as the glucose concentration at t = 120 min.…”
Section: Methodsmentioning
confidence: 99%